2019
DOI: 10.1088/1367-2630/ab0a94
|View full text |Cite
|
Sign up to set email alerts
|

Heat and water vapor transfer in the wake of a falling ice sphere and its implication for secondary ice formation in clouds

Abstract: We perform direct numerical simulations of the settling of an ice sphere in an ambient fluid accounting for heat and mass transfer with the aim of studying in a meteorological context the case of falling graupel in humid air. The study is motivated by the fact that falling graupels in clouds are heated by the latent heat released during the accretion of liquid water droplets. They may therefore be considerably warmer than their surrounding and evaporate water vapor, which mixes with the surrounding air in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 35 publications
0
34
0
Order By: Relevance
“…In Chouippe et al (2019) we have shown that buoyant forces due to density variations within the fluid phase caused by variations in temperature and concentration are negligible at the parameter point of interest. The flow can then be approximated by the incompressible Navier-Stokes equations,…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…In Chouippe et al (2019) we have shown that buoyant forces due to density variations within the fluid phase caused by variations in temperature and concentration are negligible at the parameter point of interest. The flow can then be approximated by the incompressible Navier-Stokes equations,…”
Section: Methodsmentioning
confidence: 94%
“…In this work we utilize the numerical framework previously presented in Chouippe et al (2019) and model the hydrometeor as a sphere with constant diameter D, constant surface temperature T p and a constant vapor pressure e v,p at its surface. The latter is determined by the assumption of local equilibrium at the surface, and thus, corresponds to the saturation vapor pressure e sat,j at T p .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations